Peran Ekstrak Kulit Batang Leea angulata Pada Tahap Proliferasi dalam Proses Penyembuhan Luka Kulit Mencit (Mus musculus): Role of Leea angulata Bark Extract on Proliferation Phase of Wound Healing Process in Mouse Skin (Mus musculus) - Hidayah, Thauhidayatul; Barlian, Anggraini; Hidayah, THAUHIDAYATUL HIDAYAH (Departemen Biologi, Institut Pertanian Bogor, 2021)
Leea angulata is a commonly plant used by the Sasak people as a medicine to heal the wounds, but the effects of L. angulata on wound healing process has not been studied. The aim of this research are to determine the effects of L. angulata bark extracts on wound healing of mouse skin and its influence on the localization of FGF2. 1% of L. angulata bark extracts (P1%) on day 7 can accelerate wound closure amounted at 94.66%, Deep and Superficial Contraction Index of 0.96 and 0.1, epidermis Index and remodeling index of 1.55 and 0.81. L. angulata bark extracts stimulates the synthesis of FGF2 early (3rd day ) compared to the postive control group (5th day). FGF2 in P1% group wa found in epithelial cells in the hair follicles, fibroblasts cell in granulation tissue and epithelial cells in the epidermis. In the positive control group FGF2 was found in in epithelial cell of hair follicle, while in the negative control group, FGF2 undetectable. FGF2 in P1% group detected earlier than the positive control, showing the process of proliferation in P1% accelerated. The results confirm the L. angulata bark extracts accelerate the wound healing in proliferation phase and influence localization of FGF2 in the wound area. Keywords : Leea angulata, wound healing, FGF2, immunohistochemistry